Verruca punica, a new species of verrucomorph barnacle (Crustacea, Cirripedia, Thoracica) from the Lower Danian (Palaeocene) of Tunisia - Buckeridge, John S.; Jagt, John W. M.; Speijer, Robert P. (Zootaxa, 2008)
The discovery of a near-complete shell wall of a small verrucid barnacle from the Lower Danian (Palaeocene) portion of the El Haria Formation as exposed in the El Kef area (northwest Tunisia), permits its description as a new species with characters that, although conforming primarily to Verruca sensu stricto, show some similarities to Altiverruca Pilsbry, 1916, a genus that is not yet known from the fossil record. The present material extends the known geographic distribution of fossil verrucids, and constitutes one of the earliest species of Verruca to be documented subsequent to the Cretaceous/Palaeogene (K/Pg) boundary mass extinction event.